Modern Approaches for Improved Healthcare Access and Efficiency: A Critical Analysis - Al Ghufaynah , Mansour Mana Moslih; Alabbas , Salem Mana Musleh; Al Abbas, Saleh Mahdi Abdullah; Alabbas , Hadi Mana Musleh; Albbas, Abdullah Mohammed; Alshoaibi, Bader Mohammed Hadi; Alabbas, Hamad Mohammed Hadi; Alrashah, Abdullah Saleh Salem; Almakrami , Ali Mansoor Ali; Alzulayq , Fawaz Mana (Journal of Ecohumanism, 2024)
The rapid advancement of technology and the evolving needs of healthcare systems have spurred the development of innovative approaches aimed at improving healthcare access and efficiency. This article critically analyzes modern methods, including telemedicine, artificial intelligence (AI), electronic health records (EHR), and integrated care models, exploring their effectiveness, challenges, and impact on stakeholders. Through a balanced examination of case studies, this study highlights both successful implementations and areas of concern, such as disparities in digital accessibility, data security, and system interoperability. The findings underscore the transformative potential of these approaches while calling attention to the regulatory and ethical considerations that accompany them. Recommendations for future strategies emphasize policy development, technology enhancements, and global collaboration to ensure equitable and efficient healthcare access. This analysis offers healthcare practitioners, policymakers, and researchers insights into optimizing these modern solutions while mitigating risks, ultimately fostering a more resilient and inclusive healthcare system.